Coping with the Global Financial Crisis : Challenges Facing Low-Income Countries - Fabrizio, Stefania (Washington, D.C. : International Monetary Fund, 2010)
This forthcoming title in the Departmental Paper Series describes the special challenges facing low-income countries as economic growth contracts by an estimated 1.1 percent globally. Coping with the Crisis: Challenges Facing Low-Income Countries provides an assessment of the implications of the financial crisis for low-income countries, evaluates the short-term macroeconomic outlook for these countries, and discusses the policy challenges they face. Chapters cover the outlook for global economic growth and commodity prices, an overview of how low-income countries have been affected, fiscal policy, monetary and exchange rate policy responses, potential external financing needs and how the international community, including the IMF, can help countries meet them. The challenges ahead for low-income countries are delineated, including debt vulnerabilities and the need for countries to develop well-regulated local capital markets and banking systems, as well as enhanced public sector efficiency.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet